2021
DOI: 10.7150/jca.59892
|View full text |Cite
|
Sign up to set email alerts
|

Priority of PET-CT vs CT Thorax for EBUS-TBNA 22G vs 19G: Mesothorax Lymphadenopathy

Abstract: Introduction: Lung lesions and undiagnosed mesothorax lymphadenopathy is an issue that several doctors face in the everyday clinical practice. PET-CT and CT of the thorax are usually the first examinations to identify characteristics of the lesions before biopsy. Patients and Methods: We performed a retrospective study with 450 patients that had EBUS-TBNA with 22G, Upgraded 22G and 19G needles with and without PET-CT in order to identify the cost effeteness of performing EBUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…It has been previously presented that indifferent of the needle size the sample is enough for diagnosis and molecular next generation sequencing (NGS) investigation for lung cancer and other metastatic cancers in the lung parenchyma 5 , 15 , 18 . In a recent study it was observed that the 19G needle when compared to 22G needle has a larger sample size and it has a higher diagnostic sensitivity for lymphoma 19 , 20 . This information is in accordance with previous publications with the esophageal ultrasound (EUS) where the gastroenterologists used larger 19G needles 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously presented that indifferent of the needle size the sample is enough for diagnosis and molecular next generation sequencing (NGS) investigation for lung cancer and other metastatic cancers in the lung parenchyma 5 , 15 , 18 . In a recent study it was observed that the 19G needle when compared to 22G needle has a larger sample size and it has a higher diagnostic sensitivity for lymphoma 19 , 20 . This information is in accordance with previous publications with the esophageal ultrasound (EUS) where the gastroenterologists used larger 19G needles 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of nodules ≥1cm in diameter we can perform positron emission tomography (PET-CT) as a method to acquire information regarding the metabolic rate and evaluate the lymphnode stations in the thorax and check for distant metastasis. [8] In the case of pulmonary nodules less than 1cm the PET-CT usually cannot provide us with information regarding the metabolic rate due to the technical limitations of the method. However; we should not forget that even large nodules, large lymphnode stations can be false negative due to the low metabolic rate of the cancer disease.…”
Section: Introductionmentioning
confidence: 99%
“…Non-small cell lung cancer is still diagnosed at advanced stage and systemic treatment administration is required. We have nowadays novel tools for the diagnosis and staging of lung cancer like radial-ebus, electromagnetic navigation and convex probe-ebus [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ]. However; we still need a successful lung cancer screening program for early lung cancer diagnosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%